CLAUSE COMPLEX AND EXPERIENTIAL REALIZATION IN COURT TEXTS (BALI BOMB CASE I): A SYSTEMIC FUNCTIONAL LINGUISTICS STUDY - Setia, Eddy; Sutjaja, I Gusti Made; Saragih, Amrin; Putrayadnya, Ida Bagus (e-Journal of Linguistics; Vol. 3. 1 Januari 2009 No. 1, 2009)
-